Thinking Green Chemistry: beyond the technological optimism and pitfalls of possible slogan - Pitanga, Ângelo Francklin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Faced with a society organized as the basis of voracious economic and mechanistic paradigm it is necessary to question some contradictions, among them, how to keep the frenetic rhythms of production and consumption on a planet which has finite source of material? And which for some years it has already given clear signs of depletion, primarily associated with quality in the provision of basic environmental services. Thus, it is important to discuss the influence of ideas such as: sustainable development, technological advances, principles of thermodynamics, thermodynamic-ecological paradigm and green chemistry. In the meantime this essay aims to make a reflection/discussion on three important issues: 1) The emergence of some myths credited by technological optimism from the fundamentals of thermodynamics; 2) The ownership of the philosophy of Green Chemistry as a slogan; 3) The importance of education in green chemistry, on the premise of being an integrated, cross-sectional component and a prospective character leading to deeper understanding of environmental issues.